Reestablishment of occlusion with prosthesis and composite resin restorations - Garcia, Alício Rosalino [UNESP]; Sundfeld, Renato Herman [UNESP]; Alexandre, Rodrigo Sversut de [UNESP] (Tokyo Dental College, 2009)
Here, we present a case report on prosthetic reconstruction of posterior teeth and composite resin restoration of anterior teeth yielding considerable esthetic improvement, reestablishment of disocclusion guides and function.
Keywords: Occlusion; Composite resin; Prosthesis